Splicing factor mutations in hematologic malignancies - Chen, Sisi; Benbarche, Salima; Abdel-Wahab, Omar (Blood, 2021)
Mutations in genes encoding RNA splicing factors were discovered nearly 10 years ago and are now understood to be among the most recurrent genetic abnormalities in patients with all forms of myeloid neoplasms and several types of lymphoproliferative disorders, as well as subjects with clonal hematopoiesis. These discoveries implicate aberrant RNA splicing, the process by which precursor RNA is converted into mature messenger RNA, in the development of clonal hematopoietic conditions. Both the protein and the RNA components of the splicing machinery are affected by mutations at highly specific residues, and a number of these mutations alter splicing in a manner distinct from loss of function. Importantly, cells bearing these mutations have now been shown to generate mRNA species with novel aberrant sequences, some of which may be critical to disease pathogenesis and/or novel targets for therapy. These findings have opened new avenues of research to understand biological pathways disrupted by altered splicing. In parallel, multiple studies have revealed that cells bearing change-of-function mutation in splicing factors are preferentially sensitized to any further genetic or chemical perturbations of the splicing machinery. These discoveries are now being pursued in several early-phase clinical trials using molecules with diverse mechanisms of action. Here, we review the molecular effects of splicing factor mutations on splicing, the mechanisms by which these mutations drive clonal transformation of hematopoietic cells, and the development of new therapeutics targeting these genetic subsets of hematopoietic malignancies.